Hilirisasi Produk Pembelajaran Mahasiswa melalui Pemanfaatan Buku Cerita Bergambar di Lembaga PAUD - Nia Fatmawati; Nopiana Nopiana (Prodi PGSD Unsultra, 2026)
Higher education institutions have a responsibility to ensure that learning outcomes provide tangible benefits to society through community service activities. One form of implementation is the downstreaming of student learning products, particularly picture storybooks developed in the Storytelling course, for use in Early Childhood Education (ECE) institutions. This community service program aimed to facilitate the downstreaming of student learning products through the utilization of picture storybooks as supporting media for early childhood literacy. The implementation process included identifying partner needs, coordinating with ECE institutions, distributing the picture storybooks, providing mentoring on their use in storytelling activities, and conducting evaluations through classroom observations and teacher interviews. The results indicated that the picture storybooks were well received because they were appropriate for children's developmental characteristics, enriched learning resources, increased the variety of literacy activities, and assisted teachers in delivering stories in a more engaging manner. Furthermore, the program successfully demonstrated the downstreaming of student learning products, enabling academic outputs to be utilized sustainably by the community. Therefore, this community service initiative strengthened the partnership between higher education institutions and ECE institutions in supporting the improvement of early childhood literacy learning quality.